RIS-Assisted Terahertz Communications for 6G Networks: A Comprehensive Overview - Alok Kumar; Sanjeev Sharma; M. Hemanta Kumar; Ghanshyam Singh (IEEE Access)
The integration of multiple-input multiple-output (MIMO) technology with reconfigurable intelligent surfaces (RIS) in Terahertz (THz) communication systems has emerged as a promising approach to address the challenges and exploit the opportunities in next-generation wireless networks. This technical review provides a systematic state-of-the-art research and developments toward MIMO-based RIS-supported THz communication, systems focus on the potential research opportunities, challenges, and emerging applications of this innovative technology. Further, this paper explores the combined benefits of integrating MIMO with RIS to improve link reliability, along with the associated system-level design challenges. Furthermore, we discuss various aspects of MIMO-based RIS-supported THz communication, such as channel modeling, channel estimation, beamforming techniques, beam split effect resource allocation strategies, and performance evaluation metrics. Moreover, the role of artificial intelligence and machine learning (AI/ML) in the design of RIS-empowered THz wireless communication systems is also discussed.